1997
DOI: 10.1007/s001250050691
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β receptor and fibronectin expressions in aortic smooth muscle cells in diabetic rats

Abstract: We have previously reported that cultured aortic smooth muscle cells (SMC) and medial layers of arteries of diabetic rats and rabbits express more platelet-derived growth factor (PDGF) b -receptor than those of non-diabetic animals [1,2]. In addition, diabetic SMC grow much faster than control SMC specifically in reponse to A-B heterodimer and B-B homodimer of PDGF, suggesting that the overexpression of PDGF b -receptor in SMC is a causative element in the accelerated growth of diabetic SMC. In an in vivo stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 28 publications
2
19
0
1
Order By: Relevance
“…PDGF is powerful SMC mitogen resulting in SMC migration and proliferation (28, 33) and released from injured endothelial cells in diabetics (28). In previous studies, researchers have reported that arterial SMCs and medial layers of arteries of diabetic rats express more PDGF β-receptor than those of control rats (32,34,35). Poulter et al (36) and Askari et al (31) suggested that proliferation of SMCs in the tunica media caused a increase in collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…PDGF is powerful SMC mitogen resulting in SMC migration and proliferation (28, 33) and released from injured endothelial cells in diabetics (28). In previous studies, researchers have reported that arterial SMCs and medial layers of arteries of diabetic rats express more PDGF β-receptor than those of control rats (32,34,35). Poulter et al (36) and Askari et al (31) suggested that proliferation of SMCs in the tunica media caused a increase in collagen synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that transcriptional repression of the T␤R gene may be a major mechanism in inactivating T␤R in tumor cells (46). In contrast, up-regulation of T␤R expression has been demonstrated in fibrotic diseases, such as SSc, localized scleroderma, hepatic fibrosis, idiopathic hypertrophic obstructive cardiomyopathy, and atherosclerosis (22,26,(47)(48)(49)(50). Upregulation of T␤R expression would result in the deposition of ECM components, which are the chief pathologic features of fibrotic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…18 For the identification of OPN, we used the anti-human OPN antibody (10A16, 5 g/mL) as well as the anti-rat OPN antibody (MPIIIB10, 1:250 dilution), which also cross-reacts with human OPN, according to the manufacturer's instructions. For the identification of SMCs, we used the anti-␣-smooth muscle actin antibody (1A4, 1:1000 dilution).…”
Section: Immunohistochemistrymentioning
confidence: 99%